Chapter Neuroscienze per l'architettura - Albright, Thomas (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Discusses the Indian design treatise the Vaastu Veda in relation to visual neuroscience. Relates visual perception in architecture to functional organisation of the brain. Relates Hubel and Weisel's orientation sensitivity to the sense of order and pleasure imparted by the regularity of colonnades and cable stay bridges. Suggests aspects of perception facilitated by neuronal architecture and the dynamic between familiarity and novelty, plasticity and visual attunement.